Étude sur les besoins spécifiques des femmes immigrantes francophones en situation minoritaire - Alliance des femmes de la francophonie canadienne (L’Alliance des femmes de la francophonie canadienne (AFFC), 2021)

Healthcare Access of Autistic Language Minorities: The Case of English Official Language Minorities in Quebec, Canada - Amantayev, Nariman; Rao, Sabrina; Nadig, Aparna (Minorités linguistiques et société, 2025)
Abstract English and French are both official languages in Canada. Whereas official language minorities (English speakers in Quebec, French speakers in the rest of Canada) face healthcare barriers and poor health outcomes, autistic individuals and their families also struggle with accessing healthcare. We examined healthcare access at the intersection of these groups: the autistic community, including English minority-language speakers from Quebec, French majority-language speakers from Quebec, and English majority-language speakers from elsewhere in Canada (n = 165). Linguistic minorities reported poorer access to publicly-funded services and lower satisfaction that their language needs were being met than did linguistic majorities. Foreign-born English speakers also experienced poorer access than their Canadian-born counterparts. These preliminary findings suggest that autistic language minorities face known barriers to accessing healthcare, potentially at a higher rate than that experienced by language minorities in general. Résumé L’anglais et le français sont les langues officielles du Canada. Les minorités de langue officielle (anglophones au Québec, francophones hors Québec) font face à des obstacles en matière de santé, tout comme les personnes autistes et leurs familles. Nous avons examiné l’accès aux services de santé à l’intersection de ces groupes : la communauté autiste, incluant des anglophones (minoritaires) et francophones (majoritaires) du Québec, ainsi que des anglophones (majoritaires) du reste du Canada (n = 165). Les minorités linguistiques déclarent un accès plus difficile aux services de santé publics et une moindre satisfaction quant à la prise en compte de leurs besoins linguistiques, comparativement aux majorités linguistiques. Les anglophones nés à l’étranger rapportent également un accès plus difficile que leurs pairs nés au Canada. Ces résultats préliminaires suggèrent que les minorités linguistiques autistes font face à des obstacles connus en matière d’accès aux soins, possiblement à un degré plus élevé.

Distance, access and equity: A cross-sectional geospatial analysis of disparities in acess to primary care for French-only speakers in Ottawa, Ontario - Belanger, Christopher; Carr, Kady; Peixoto, Cayden; Bjerre, Lise M. (CMAJ Open, 2023)
Background: Although language concordance between patients and primary care physicians results in better quality of care and health outcomes, little research has explored inequities in travel burden to access primary care people of linguistic minority groups in Canada. We sought to investigate the travel burden of language-concordant primary care among people who speak French but not English (French-only speakers) and the general public in Ottawa, Ontario, and any inequities in access across language groups and neighbourhood ruralities. Methods: Using a novel computational method, we estimated travel burden to language-concordant primary care for the general population and French-only speakers in Ottawa. We used language and population data from Statistics Canada’s 2016 Census, neighbourhood demographics from the Ottawa Neighbourhood Study, and collected the main practice location and language of primary care physicians from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Results: We included data from 869 primary care physicians and 916 855 patients. Overall, French-only speakers faced greater travel burdens than the general population to access language-concordant primary care. Median differences in travel burden were statistically significant but small (median difference in drive time 0.61 min, p < 0.001, interquartile range 0.26–1.17 min), but inequities in travel burden between groups were larger among people living in rural neighbourhoods. Interpretation: French-only speakers in Ottawa face modest — but statistically significant — overall inequities in travel burden when accessing primary care, compared with the general population, and higher inequities in specific neighbourhoods. Our results are of interest to policy-makers and health system planners, and our methods can be replicated and used as comparative benchmarks to quantify access disparities for other services and regions across Canada.

Bien dans notre peau: Élaboration d’un outil de diagnostic pour informer la conception et l’évaluation de services et partenariats sécuritaires, inclusifs et équitables pour toute personne 2ELGBTQ+ d’expression française au Manitoba - Courcelles, Rémi; Hardy, Stephan; Prada, Kevin (Santé Canada, 2023)

Healthcare Service Utilization and Perceived Gaps: The Experience of French-Speaking 2S/LGBTQI+ People in Manitoba - de Moissac, Danielle; Prada, Kevin; Gueye, Ndeye Rokhaya; Avanthay-Strus, Jacqueline; Hardy, Stephan (Healthcare Policy, 2024)
Ethnolinguistically diverse 2S/LGBTQI+ (two-spirit, lesbian, gay, bisexual, transgender, queer and intersex) populations have unique healthcare needs and experience health inequities compared to their cisgender or heterosexual peers. This community-based participatory study sought to describe the profile and healthcare needs and experiences of official language minority French-speaking 2S/LGBTQI+ adults in Manitoba. Participants (N = 80) reported that gender and sexual identity were often concealed from service providers; many respondents faced discrimination based on their ethnolinguistic and sexual identities. Service gaps are identified pertaining to mental and sexual health; locating 2S/LGBTQI+-friendly, patient-centred care in French is difficult. Policy and practice should address systemic inequity and discrimination experienced by this equity-seeking population.

Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Statistique Canada, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Statistics Canada, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Language barriers and healthcare access: a qualitative study in the Volta Region of Ghana - Glover-Meni, Nathaniel; Nyarko, Joy Ato; Agbezorlie, Peter K.; Agyei, Dominic Dankwah (Journal of Communication in Healthcare, 2024)
Background The study explores the language barriers between two language minority populations and healthcare professionals in the Volta Region of Ghana. Methods An interpretive description with a qualitative approach to data collection and analysis was used. This study was carried out in the Tafi-Atome and Avatime-Vane communities, the Hohoe Municipal Hospital and the Margaret Marquart Catholic Hospital in the Kpando Municipality. In all, 46 respondents comprising 19 purposively sampled community members (patients) from the two selected communities and 27 conveniently sampled healthcare professionals from the two health facilities were interviewed. The face-to-face in-depth interviews were audio-recorded, transcribed and thematically analysed. Results The study revealed a barrier in language use between healthcare professionals and patients from the two language minority communities. While healthcare professionals preferred to use English, Akan and Ewe, the patients, on the other hand, preferred their native languages, which are Sideme and Tegbor. The services of unqualified interpreters were utilised by both healthcare professionals and patients. Study participants were aware of these challenges, which prevented the patients from receiving optimum healthcare services, and the healthcare workers from delivering client-centred healthcare services. Conclusions The presence of communication challenges emanating from language barriers between healthcare professionals and patients should be considered as a key hindrance to the attainment of the Sustainable Development Goal Three (SDG3), which aims to promote health and well-being at all ages. Therefore, stakeholders in the healthcare delivery system in Ghana need to prioritize stronger communication and translation practices and policies.

Argumentaire pour la promotion d’une offre de service santé de qualité dans la langue maternelle des clients au Nunavut - Réseau Santé en français au Nunavut (2021)

À la rencontre des communautés acadiennes et francophones et de leurs enjeux en santé - Réseau Santé Nouvelle Écosse (Réseau santé en français de Nouvelle-Écosse, 2021)

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2025g

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html fs-code-orig: Savard-2025h

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Agir ensemble pour une Petite enfance en santé dans les communautés francophones et acadienne en situation minoritaire : Résultats et impacts du programme Petite enfance en santé 2024-2025 - Société Santé en français et les Réseaux de santé en français (2025)

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)
fs-ref-orig: van Kemenade, S., Benoît, J., Savard, S. et Savard, J. (2025). Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html. fs-code-orig: van Kemenade-2025d

Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador) - van Kemenade, Solange; Michel, Jean Nephetaly; Savard, Jacinthe; Benoît, Josée (2021)
fs-ref-orig: van Kemenade, S., Michel, J.N., Savard, J. & Benoît, J. (2021, mise à jour 2025). Pratique # 23 : Navigateur francophone du système de santé (Terre-Neuve-et-Labrador). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https:// www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: van Kemenade-2025a

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.